1997
DOI: 10.1017/s1037291100001266
|View full text |Cite
|
Sign up to set email alerts
|

A wellness approach to the management of traumatic loss in schools: an examination of teachers' stress responses and coping strategies, and school response mechanisms.

Abstract: This study was a qualitative examination of the stress responses and coping strategies of 21 teachers (12 women & 9 men), and school response mechanisms following a critical incident involving the death of a student or colleague. In order to explore the possibility that deaths of a relatively common nature can evoke high stress and grief responses, exceptional or large scale events, or those generating widespread public or media attention, were excluded. Findings showed that the impact on participants was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Research has also found the police environment to be prone to increased burnout symptoms such as exhaustion, negativity, cynicism and devaluation of self and others (Johnson, Todd & Subramanian, 2005), post traumatic stress disorder (PTSD) (Jackson, 2003;Violanti, 1997), suicide ideation (Rothmann & Van Rensburg, 2002;Rothmann & Strijdom, 2002) suicide (Mabe, 2004;Rothmann and Van Rensburg, 2002), substance abuse (Padayachee & Singh, 2003;Rothmann & Van Rensburg, 2002) and job withdrawal (Leontaridi & Ward, 2002;Plani, Bowley & Goosen, 2003;Schonteich, 2003).…”
Section: Police Work In Contextmentioning
confidence: 99%
“…Research has also found the police environment to be prone to increased burnout symptoms such as exhaustion, negativity, cynicism and devaluation of self and others (Johnson, Todd & Subramanian, 2005), post traumatic stress disorder (PTSD) (Jackson, 2003;Violanti, 1997), suicide ideation (Rothmann & Van Rensburg, 2002;Rothmann & Strijdom, 2002) suicide (Mabe, 2004;Rothmann and Van Rensburg, 2002), substance abuse (Padayachee & Singh, 2003;Rothmann & Van Rensburg, 2002) and job withdrawal (Leontaridi & Ward, 2002;Plani, Bowley & Goosen, 2003;Schonteich, 2003).…”
Section: Police Work In Contextmentioning
confidence: 99%
“…Another common area of difficulty relating to competence is knowing the limits of your skills or expertise. For example, many a fool keen to be helpful has rushed in running a program where they cannot control twelve angry teenagers, or trying to take over after a crisis and not allowing the school staff to respond in a way that suits them, or enhances their coping resources (Jackson & Bates, 1997).…”
Section: Professional Competencementioning
confidence: 99%